A STUDY OF STUDENTS’ PERCEPTION TOWARDS THE CORRECTIVE FEEDBACKS USED BY THE TEACHER IN CORRECTING THE STUDENTS’ WRITING PROBLEMS - Asis Warni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research aimed to find out the students’ perception towards the corrective feedbacks used by the teacher in correctinng the students’ writing problems. The reseach employed descriptive method. The sample of this research was selected by using random sampling technique. The instruments of data collection was a students’ checklist. The data of the students’ perception towards the corrective feedback stated that 59,09% students said that direct corrective feedback help them to understand what to do to correct their errors. Next, the result shown that 54,55% of the students also mentioned that they can notice and understand their errors about punctuation, spelling, and capitalization through indirect corrective feedback easily. Furthermore, half of them or 50% of the sample students told that indirect corrective feedback encouraged them to write in a better topic and details. In conclusion, the corrective feedbacks improve student’s ability in writing especially descriptive text and the students have positive perceptions about the corrective feedbacks.